CORRELATION ANALYSIS OF SHARIA CAPITAL MARKET GROWTH WITH INDEX SHARIA CAPITAL MARKET PERFORMANCE - Anisya Wulan Purnama (RADJA PUBLIKA, 2023)
This research is intended for informative purposes and adds insight regarding the capital market, the Islamic capital market, the growth of the Islamic capital market in Indonesia which is analyzed based on its correlation with the Islamic capital market performance index compared to the conventional capital market performance index which is tested through 3 test analyzes using the index Sharpe, Treynor, and Jensen. This research was conducted using data from 2007 to 2019. This study aims to provide information related to the relationship between the performance index of the Islamic capital market and its growth over time (2013-2019).